2009
DOI: 10.1038/nnano.2009.49
|View full text |Cite
|
Sign up to set email alerts
|

An electric current spike linked to nanoscale plasticity

Abstract: The increase in semiconductor conductivity that occurs when a hard indenter is pressed into its surface has been recognized for years, and nanoindentation experiments have provided numerous insights into the mechanical properties of materials. In particular, such experiments have revealed so called pop-in events, where the indenter suddenly enters deeper into the material without any additional force being applied; these mark the onset of the elastic-plastic transition. Here, we report the observation of a cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 31 publications
5
60
2
Order By: Relevance
“…Our research revealed that this is not always true: instead of dislocation activity, nanoscale deformation may simply be due to phase transformation (semiconductor → metal), as predicted for GaAs by our earlier experiments and atomistic calculations [3]. Using a novel conductive nanoindentation technique, which is highly sensitive to structural changes under pressure [4], we discovered the essential link between this electrical phenomenon (current spike) and the mechanical transient (pop-in) exhibited by GaAs exclusively during nanoscale deformation. The results obtained for GaAs and dramatic impact of crystal imperfections on the functional properties of semiconductors have motivated our studying the nanoscale deformation of Si nanoparticles that is addressed in the present paper.…”
Section: Introductionmentioning
confidence: 62%
“…Our research revealed that this is not always true: instead of dislocation activity, nanoscale deformation may simply be due to phase transformation (semiconductor → metal), as predicted for GaAs by our earlier experiments and atomistic calculations [3]. Using a novel conductive nanoindentation technique, which is highly sensitive to structural changes under pressure [4], we discovered the essential link between this electrical phenomenon (current spike) and the mechanical transient (pop-in) exhibited by GaAs exclusively during nanoscale deformation. The results obtained for GaAs and dramatic impact of crystal imperfections on the functional properties of semiconductors have motivated our studying the nanoscale deformation of Si nanoparticles that is addressed in the present paper.…”
Section: Introductionmentioning
confidence: 62%
“…2a). The detected singularity on the loading part of P −h curves for GaSb may stem from different structural effects such as phase transition to another crystalline structure (similarly to zinc-blende → rock-salt transition reported for GaAs [7]) or defects activity. Indeed, similarly to GaAs the phase transition was observed in GaSb at 4.05 GPa [18], and it may involve as well the vacancy nucleation processes [19].…”
Section: /2 Max Value (C)mentioning
confidence: 87%
“…While the nanomechanical properties of numerous semiconductors had already been studied (see e.g., Refs. [7][8][9]), there is lack of systematic data about mechanical behavior of the important GaSb crystal. Consequently, our research addresses the nanoindentation probing of this interesting material.…”
Section: Introductionmentioning
confidence: 99%
“…The nanoECR module has been previously used in a high-resolution application to investigate an electrical current spike associated with nanoscale plasticity in gallium arsenide. 25 The commercial nanoECR set-up was designed to measure relatively high resistances in semiconductor samples, and has been modified to facilitate the measurement of subOhm resistances occurring in individual MPS. The aforementioned custom conductive substrates were connected directly to the current and voltage leads in the Triboindenter, bypassing the nanoECR stage.…”
Section: Methodsmentioning
confidence: 99%